Теоретико-практичні аспекти організації психологічної підготовки майбутнього офіцера технічного профіля до діяльності в особливих умовах - Коваль, С. М.; Koval, S. M.; Кучеренко, С. М.; Kucherenko, S. M.; Назаров, О. О.; Nazarov, O. O. (Габітус. - 2020. - Вип. 18, т. 1. - С. 86-90, 2020)
Визначено основні цілі, завдання, функції, принципи, особливості психологічної підготовки майбутніх офіцерів технічного профіля. Розглянуто чинники успішності їх професійної діяльності, якими є ресурсні можливості людини, які включають мотиваційні, емоційно-вольові якості майбутніх офіцерів, використання саморегуляції станів під час виконання професійних функцій в особливих умовах.

The article analyzes the existing approaches to the development of a system of psychological training for specialists working in special conditions, reveals its main provisions and principles. The main goals, tasks, functions, principles, features of the psychological training of future technical officers have been determined. The factors of the success of their professional activities are considered, which are the resource capabilities of a person, including the motivational, emotional and volitional qualities of future officers, the use of self-regulation of states when performing professional functions in special conditions. It is determined that the psychological training of cadets of a technical profile should be based on knowledge of the characteristics of professional activity, which allow one to determine the normative technical and technological factors of the functioning and interaction of a specialist, while typical situations of professional activity, normative models of behavior and ways of solving professional problems, the main stages, should be considered, patterns and technologies for the development of officer’s professionalism. Considerable attention should be paid to the formation of a stable system of positive professional motives cadets, which should include priority motives for educational and professional activities, motivation for technical and engineering activities, professional technical orientation, the relationship between achievement motivation and volitional qualities. An important element of the psychological training of future officers of a technical profile is the formation of professional thinking, which includes technical, technological, organizational, is an element of the content of training, a determinant of the development of subject experience, allows the cadet to provide a comprehensive impact on the solution of the assigned tasks, their development, to promote the development of actions adequate to the corresponding situations, algorithms of activity, behavior. The formation of professional cognitive motives, teaching rational methods of mental activity allows you to create favorable conditions for the development of technical thinking. The approach to psychological training of future officers of a technical profile which includes psychological substantiation of model of the specialist of a technical profile, formation of motives of educational and professional activity, motivation to technical and engineering activity, professional thinking.

Определены основные цели, задачи, функции, принципы, особенности психологической подготовки будущих офицеров технического профиля. Рассмотрены факторы успешности их профессиональной деятельности, ресурсные возможности человека, включающие мотивационные, эмоционально-волевые качества будущих офицеров, использование саморегуляции состояний при выполнении профессиональных функций в особых условиях.
Theoretical and practical aspects of the organization of psychological preparation of the future officer of the technical profile for activity under specific conditions
Коваль, С. М. Теоретико-практичні аспекти організації психологічної підготовки майбутнього офіцера технічного профіля до діяльності в особливих умовах / Коваль С. М., Кучеренко С. М., Назаров О. О. // Габітус. - 2020. - Вип. 18, т. 1. - С. 86-90. - DOI: https://doi.org/10.32843/2663- 5208.2020.18.1.15.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; професійна діяльність; professional activity; профессиональная деятельность; професійна підготовка; professional training; профессиональная подготовка; майбутні офіцери технічного профіля; future officers of the technical profile; будущие офицеры технического профиля; професійна мотивація; professional motivation; профессиональная мотивация; психологічна підготовка; psychological preparation; психологическая подготовка; особливі умови діяльності; special conditions of activity; особые условия деятельности